Determinants of adolescents’ perceptions on access to healthcare services in the Kingdom of Saudi Arabia: Jeeluna national survey findings - Shahenaz Najjar; Fadia AlBuhairan; Mayssa Saade; Sahar Abdalla (BMJ Open, 2021)
Objectives The study aimed at identifying the determinants of adolescents’ access to healthcare services.Setting Intermediate and secondary schools across all 13 regions in the Kingdom of Saudi Arabia (KSA) from 2011 to 2012 through the Jeeluna national school-based survey.Participants Intermediate and secondary school students participated in the study. A multistage, cluster, random sampling technique was used. Participants responded to a self-administered questionnaire that addressed several domains.Main outcome measure Adolescents’ perception of access to healthcare services.Results Twenty-five per cent of participants reported difficulty in accessing healthcare. Women, early (younger) adolescents and adolescents with three siblings were less likely to report difficulty in accessing healthcare than men, late (older) adolescents and those with fewer than three siblings. Adolescents from low-income families and those with either mental or physical illness were more likely to report difficulty in accessing healthcare than adolescents from higher income families and those without mental or physical illnesses.Conclusions Disparities in access to care exist between certain subpopulations of adolescents. Efforts are needed to support enhancing access and making it more equitable. Training for healthcare professionals and targeted health policies are necessary to improve adolescents’ access to health services in the KSA.Trial registration number RC08-092; King Abdullah International Medical Research Centre.